Peranan Pembimbing Kemasyarakatan dalam Program Asimilasi Rumah di Balai Pemasyarakatan Kelas I Padang - Hani Salsabila, Aisha; Khaidir, Afriva (Policy, Law and Political Research Center, 2024)
This study aims to describe the role of community supervisors in the home assimilation program at the Class I Padang Correctional Center (Bapas) and the obstacles faced in implementing the program. This research uses a qualitative approach with descriptive methods. The selection of informants was done through a purposive sampling technique. Data were collected through interviews, observation and documentation. Data validity was tested using source triangulation and technique triangulation. Data analysis was conducted through data reduction, presentation, and conclusion drawing. The results showed that community supervisors play a facilitative role by serving clients who are required to report, an educational role by providing personality guidance activities, and a technical role by collecting data and coordinating with related parties in client supervision. The obstacles faced include (1) loss of contact with clients and non-fulfilment of reporting obligations by clients, (2) unknown client guarantors (not from family), (3) the location of clients who are in one area with victims, and (4) the limited number of human resources while the coverage of the work area is quite extensive.